2017
DOI: 10.1016/j.bbmt.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Age in Neurocognitive Functioning among Adult Allogeneic Hematopoietic Cell Transplant Recipients

Abstract: Improvements in supportive care have enabled allogeneic hematopoietic cell transplant (HCT) to be performed in increasingly older patients. HCT is associated with neurocognitive impairment, which may be exacerbated in older adults due to normal neurocognitive decline associated with aging. The goal of this study was to evaluate whether increased age in allogeneic HCT recipients is associated with worse neurocognitive outcomes over time relative to a matched sample of individuals without cancer. Patients (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Interestingly, we found that older age (65 years) was a significant predictor of worse visual working memory, to the extent of nearly a full SD (.9 SD), regardless of study cohort (ie, vorinostat-treated, autologous control subjects, allogeneic control subjects). This finding is consistent with recent studies of cognitive impairment in older patients [4,35]. Because of the potential impact of steroid use on neurocognitive function, we also included it as a covariate in our models.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, we found that older age (65 years) was a significant predictor of worse visual working memory, to the extent of nearly a full SD (.9 SD), regardless of study cohort (ie, vorinostat-treated, autologous control subjects, allogeneic control subjects). This finding is consistent with recent studies of cognitive impairment in older patients [4,35]. Because of the potential impact of steroid use on neurocognitive function, we also included it as a covariate in our models.…”
Section: Discussionsupporting
confidence: 86%
“…In the few studies that have reported findings in this population, results suggest regardless of age, HCT survivors have more neurocognitive dysfunction than healthy individuals. 25 Further, age was not associated with outcomes such as graft-versus-host disease, non-relapse mortality or overall survival. 25 …”
Section: Introductionmentioning
confidence: 86%
“…25 Further, age was not associated with outcomes such as graft-versus-host disease, non-relapse mortality or overall survival. 25 …”
Section: Introductionmentioning
confidence: 86%
“…(62, 63) Specifically, at 3 years post-HCT, reduced-intensity HCT recipients scores declined significantly (P<0.003) for executive function, verbal fluency, and working memory compared to non-cancer controls (63). The ability to manage a complex medication regimen, enjoy a hobby, and return to prior social roles is more difficult with cognitive impairment (64).…”
Section: Frailty In Hematological Malignanciesmentioning
confidence: 96%